Macromicroscopic changes of the laboratory rats kidney in norm and after immunocomprometation with enterococcus infection - Torianik, I; Myronenko, L; Peretyatko, E; Tkachyk, I (Annals of Mechnikov’s Institute, 2020)
The unification approach to the creation of the enterococcus infection model in the unlinear immunocomprometive laboratory female rats (Wistar) is presented in the article. The examinational material are in the female rats (of the 3-th- months age’s (n=60), the 165-170 g by weight). The purpose of the experiment’s are achieving by the seding enterococcus infection means of the basic structures and blood vessels of the kidney, digestive system damages, that similar with the such in a human in a case of the development of a traditional clinic pathology. The results are evaluated to character of the morphological changes (destructive and degenerative alterations, necrosis, nephropathy, inflammatory (alterative) processes. Sum upping, of capable of the achievement, we are noting carried out experiment’s efficiency and the using optimistic perspective of the extrapolative data in the capacity as a foundation for the further of the newest methods of the enterococcus infection.